Adsorption of Ferritin at Nanofaceted Al2O3 Surfaces - Pothineni, Bhanu K.; Kollmann, Sabrina; Li, Xinyang; Grundmeier, Guido; Erb, Denise J.; Keller, Adrian (International Journal of Molecular Sciences)
The influence of nanoscale surface topography on protein adsorption is highly important for numerous applications in medicine and technology. Herein, ferritin adsorption at flat and nanofaceted, single-crystalline Al2O3 surfaces is investigated using atomic force microscopy and X-ray photoelectron spectroscopy. The nanofaceted surfaces are generated by the thermal annealing of Al2O3 wafers at temperatures above 1000 °C, which leads to the formation of faceted saw-tooth-like surface topographies with periodicities of about 160 nm and amplitudes of about 15 nm. Ferritin adsorption at these nanofaceted surfaces is notably suppressed compared to the flat surface at a concentration of 10 mg/mL, which is attributed to lower adsorption affinities of the newly formed facets. Consequently, adsorption is restricted mostly to the pattern grooves, where the proteins can maximize their contact area with the surface. However, this effect depends on the protein concentration, with an inverse trend being observed at 30 mg/mL. Furthermore, different ferritin adsorption behavior is observed at topographically similar nanofacet patterns fabricated at different annealing temperatures and attributed to different step and kink densities. These results demonstrate that while protein adsorption at solid surfaces can be notably affected by nanofacet patterns, fine-tuning protein adsorption in this way requires the precise control of facet properties.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Neural Class Expression Synthesis (Extended Abstract) - Kouagou, N’Dah Jean; Heindorf, Stefan; Demir, Caglar; Ngomo, Axel-Cyrille Ngonga (NeSy)

IndQNER: Named Entity Recognition Benchmark Dataset from the Indonesian Translation of the Quran - Gusmita, Ria Hari; Firmansyah, Asep Fajar; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille (Natural Language Processing and Information Systems)
Indonesian is classified as underrepresented in the Natural Language Processing (NLP) field, despite being the tenth most spoken language in the world with 198 million speakers. The paucity of datasets is recognized as the main reason for the slow advancements in NLP research for underrepresented languages. Significant attempts were made in 2020 to address this drawback for Indonesian. The Indonesian Natural Language Understanding (IndoNLU) benchmark was introduced alongside IndoBERT pre-trained language model. The second benchmark, Indonesian Language Evaluation Montage (IndoLEM), was presented in the same year. These benchmarks support several tasks, including Named Entity Recognition (NER). However, all NER datasets are in the public domain and do not contain domain-specific datasets. To alleviate this drawback, we introduce IndQNER, a manually annotated NER benchmark dataset in the religious domain that adheres to a meticulously designed annotation guideline. Since Indonesia has the world’s largest Muslim population, we build the dataset from the Indonesian translation of the Quran. The dataset includes 2475 named entities representing 18 different classes. To assess the annotation quality of IndQNER, we perform experiments with BiLSTM and CRF-based NER, as well as IndoBERT fine-tuning. The results reveal that the first model outperforms the second model achieving 0.98 F1 points. This outcome indicates that IndQNER may be an acceptable evaluation metric for Indonesian NER tasks in the aforementioned domain, widening the research’s domain range.

My first contact with the Foodsharing Initiative - Vochatzer, Stefanie (Creative Approaches to Climate and Peace Education. An Educationr’s Guide to Using Storytelling and Art)

Life-cycle health effects of compulsory schooling - Schmitz, Hendrik; Tawiah, Beatrice Baaba
We study the effect of education on health (hospital stays, number of diagnosed conditions, self-rated poor health, and obesity) over the life-cycle in Germany, using compulsory schooling reforms as a source of exogenous variation. Our results suggest a positive correlation of health and education which increases over the life-cycle. We do not, however, find any positive local average treatment effects of an additional year of schooling on health or health care utilization for individuals up to age 79. An exception is obesity, where positive effects of schooling start to be visible around age 60 and become very large in age group 75-79. The results in age group 75-79 need to be interpreted with caution, however, due to small sample size and possible problems of attrition.
Keywords: Education; health; life-cycle effects; compulsory schooling

Housing Situations and Local COVID-19 Infection Dynamics – A Case Study With Small-Area Data - Freise, Diana; Schiele, Valentin; Schmitz, Hendrik
Keywords: General Earth and Planetary Sciences; General Environmental Science

Partial observations, coarse graining and equivariance in Koopman operator theory for large-scale dynamical systems - Peitz, Sebastian; Harder, Hans; Nüske, Feliks; Philipp, Friedrich; Schaller, Manuel; Worthmann, Karl (arXiv:2307.15325)
The Koopman operator has become an essential tool for data-driven analysis, prediction and control of complex systems, the main reason being the enormous potential of identifying linear function space representations of nonlinear dynamics from measurements. Until now, the situation where for large-scale systems, we (i) only have access to partial observations (i.e., measurements, as is very common for experimental data) or (ii) deliberately perform coarse graining (for efficiency reasons) has not been treated to its full extent. In this paper, we address the pitfall associated with this situation, that the classical EDMD algorithm does not automatically provide a Koopman operator approximation for the underlying system if we do not carefully select the number of observables. Moreover, we show that symmetries in the system dynamics can be carried over to the Koopman operator, which allows us to massively increase the model efficiency. We also briefly draw a connection to domain decomposition techniques for partial differential equations and present numerical evidence using the Kuramoto--Sivashinsky equation.

The effect of compulsory schooling on vaccination against COVID and Influenza - Monsees, Daniel; Schmitz, Hendrik
We study the effect of education on vaccination against COVID-19 and influenza in Germany and Europe. Our identification strategy makes use of changes in compulsory schooling laws and allows to estimate local average treatment effects for individuals between 59 and 91 years of age. We find no significant effect of an additional year of schooling on vaccination status in Germany. Pooling data from Europe, we conclude that schooling increases the likelihood to vaccinate against COVID by an economically negligible effect of one percentage point (zero for influenza). However, we find indications that additional schooling increases fear of side effects from COVID vaccination.
Keywords: COVID; influenza; vaccination; education; compulsory schooling

Calibration of Large Coherent MIMO Radar Arrays: Channel Imbalances and 3D Antenna Positions - Greiff, Christian; Mateos-Núñez, David; Simoni, Renato; González-Huici, Maria; Kruse, Stephan; Scheytt, J. Christoph; Kolk, Karl; Höller, Christian; Kurz, Heiko Gustav; Meinecke, Marc-Michael; Gisder, Thomas (2023 24th International Radar Symposium (IRS))
One of the main challenges for next generation automotive radars is the improvement of angular resolution to a sub-degree level. In this context, wide aperture automotive radars of 1m length or more and resolution close to 0.1° in azimuth and 0.5° in elevation could be beneficial. To enable coherent processing of arrays with such large aperture, prior (i.e offline) and online calibration are necessary: channel imbalances (gains and phases) and three dimensional coordinates of transmit and receive elements need to be determined. We propose a calibration strategy based on alternating steps between the two subtasks of i) channel imbalance estimation with ‘known’ array positions, by applying a singular value decomposition to the resulting tensor calculus problem; and ii) antenna position estimation with ’known’ channel imbalances, by numerically maximizing the Bayesian posterior probability; in both cases operating on range/Doppler snapshots of disjoint targets (with potentially unknown locations). Simulation studies based on the parameters of a MIMO 8x6 linear sparse array show promising results as long as the initial position errors do not exceed half a wavelength (2mm), beyond which we observe strong effects of ambiguity. Experimental results with real measurements show that after calibration in laboratory conditions, our MIMO 8x6 demonstrator with 50cm aperture is able to resolve two targets at the same range with angular separation at least as close as 0.4°.

NeMo.bil - Dekarbonisierung des Verkehrs mithilfe von Leichtbau-Fahrzeugschwärmen - Ostermann, Moritz; Behm, Jonathan; Marten, Thorsten; Tröster, Thomas (WerkstoffPlus Auto 13. Fachtagung für neue Fahrzeug- und Werkstoffkonzepte)

Beyond the Boolean: How Programmers Ask About, Use, and Discuss Gender - Bouma-Sims, Elijah; Acar, Yasemin (Proc. ACM Hum. Comput. Interact.)

16 Fragen, 16 Antworten: In unserer Rubrik „Lehren im Leben” stellen wir Menschen vor, die Hochschullehre gestalten. Folge 6: Dr. Nerea Vöing - Vöing, Nerea (Lehren im Leben - Blog der Stiftung Innovation in der Hochschullehre)

Ein Blick auf Lehre und Lernen in Hochschulen durch die Brille der Hochschuldidaktik" - Vöing, Nerea (Trafohaus//Lehre (Podcast der HD Sachsen))

Lehrentwicklung durch Scholarship of Teaching and Learning – mit SoTL Hochschullehre beforschen, weiterentwickeln und teilen - Vöing, Nerea; Arnold, Maik; Reisas, Sabine

Revisiting the initial reaction rates for TMS combustion and a new evidence for metastable silica nanoparticles in the gas-phase synthesis - Karakaya, Yasin; Somnitz, H.; Hermsen, A.; Gonchikzhapov, Munko; Kasper, Tina (Applications in Energy and Combustion Science)
Keywords: Metastable particles; Nanomaterials; Quartz-crystal-microbalance; Molecular-beam mass spectrometry; Tetramethylsilane; Reaction kinetics

Handling of uncertainties in the design of sustainable Additive Manufacturing products by merging Design-for-X and Scenario-Technique - Gräßler, Iris; Mozgova, Iryna; Pottebaum, Jens; Ott, Manuel; Jung, Philipp; Hesse, Philipp (Procedia CIRP ICME)
New technologies and materials carry significant potential for sustainable production and use of products. As an example, Additive Manufacturing technologies and materials promise lightweight design and energy efficient use of parts. Exhausting the full potential requires: a) consideration of uncertainties with respect to future capabilities, and b) upgradeable design guidelines to cover advancements consistently. The proposed approach merges concepts of Design-for-X with foresight algorithms of Scenario-Technique to derive actionable knowledge. It is validated by an application in the field of Additive Manufacturing, namely Metal Fused Deposition Modelling. Engineers benefit from the intuitive access to heterogeneous types of sustainability related information.
Keywords: Design-for-X; Scenario-Technique; sustainability; uncertainty; Life-Cycle Engineering; Additive Manufacturing; Circular Economy

Fiber-coupled plug-and-play heralded single photon source based on Ti:LiNbO3 and polymer technology - Kießler, Christian; Conradi, Hauke; Kleinert, Moritz; Quiring, Viktor; Herrmann, Harald; Silberhorn, Christine (Optics Express)
A reliable, but cost-effective generation of single-photon states is key for practical quantum communication systems. For real-world deployment, waveguide sources offer optimum compatibility with fiber networks and can be embedded in hybrid integrated modules. Here, we present what we believe to be the first chip-size fully integrated fiber-coupled heralded single photon source (HSPS) module based on a hybrid integration of a nonlinear lithium niobate waveguide into a polymer board. Photon pairs at 810 nm (signal) and 1550 nm (idler) are generated via parametric down-conversion pumped at 532 nm in the LiNbO3 waveguide. The pairs are split in the polymer board and routed to separate output ports. The module has a size of (2 × 1) cm^2 and is fully fiber-coupled with one pump input fiber and two output fibers. We measure a heralded second-order correlation function of g_h(2)=0.05 with a heralding efficiency of η_h=3.5% at low pump powers
Keywords: Atomic and Molecular Physics; and Optics

Scholarship of Teaching and Learning (SoTL) als Motor für eine inter- und transdisziplinäre Hochschuldidaktik - Arnold, Maik; Vöing, Nerea; Reisas, Sabine (Hochschulbildung: Lehre und Forschung)
SoTL ist eine forschungsbasierte Haltung, die die Hochschullehre verbessern und innovieren will. Das deutschsprachige SoTL-Netzwerk hat fünf Thesen formuliert, die SoTL als Grundhaltung und Motor für Lehrentwicklung betonen. Der Beitrag diskutiert diese Thesen und stellt Aktivitäten des Netzwerks vor, die SoTL an Hochschulen und Universitäten fördern und vernetzen wollen. Dabei wird auch die Rolle der »Teacher-Researcher« hervorgehoben.

Identification and prediction of standard times in machining for precision steel tubes through the usage of data analytics - Weller, Julian; Roesmann, Daniel; Eggert, Sönke; von Enzberg, Sebastian; Gräßler, Iris; Dumitrescu, Roman (Procedia CIRP)

Zur Berechnug von flüssigkeitsseitigen Stoffübergagnskoeffizienten für Strukturpackungen - Mapura Ramirez, Luz Alejandra; Kenig, Eugeny Y.

Finite-data error bounds for Koopman-based prediction and control - Nüske, Feliks; Peitz, Sebastian; Philipp, Friedrich; Schaller, Manuel; Worthmann, Karl (Journal of Nonlinear Science)
The Koopman operator has become an essential tool for data-driven approximation of dynamical (control) systems in recent years, e.g., via extended dynamic mode decomposition. Despite its popularity, convergence results and, in particular, error bounds are still quite scarce. In this paper, we derive probabilistic bounds for the approximation error and the prediction error depending on the number of training data points; for both ordinary and stochastic differential equations. Moreover, we extend our analysis to nonlinear control-affine systems using either ergodic trajectories or i.i.d. samples. Here, we exploit the linearity of the Koopman generator to obtain a bilinear system and, thus, circumvent the curse of dimensionality since we do not autonomize the system by augmenting the state by the control inputs. To the best of our knowledge, this is the first finite-data error analysis in the stochastic and/or control setting. Finally, we demonstrate the effectiveness of the proposed approach by comparing it with state-of-the-art techniques showing its superiority whenever state and control are coupled.

Multi-Objective Optimization for Sparse Deep Neural Network Training - Hotegni, Sedjro Salomon; Peitz, Sebastian; Berkemeier, Manuel Bastian (arXiv:2308.12243)
Different conflicting optimization criteria arise naturally in various Deep Learning scenarios. These can address different main tasks (i.e., in the setting of Multi-Task Learning), but also main and secondary tasks such as loss minimization versus sparsity. The usual approach is a simple weighting of the criteria, which formally only works in the convex setting. In this paper, we present a Multi-Objective Optimization algorithm using a modified Weighted Chebyshev scalarization for training Deep Neural Networks (DNNs) with respect to several tasks. By employing this scalarization technique, the algorithm can identify all optimal solutions of the original problem while reducing its complexity to a sequence of single-objective problems. The simplified problems are then solved using an Augmented Lagrangian method, enabling the use of popular optimization techniques such as Adam and Stochastic Gradient Descent, while efficaciously handling constraints. Our work aims to address the (economical and also ecological) sustainability issue of DNN models, with a particular focus on Deep Multi-Task models, which are typically designed with a very large number of weights to perform equally well on multiple tasks. Through experiments conducted on two Machine Learning datasets, we demonstrate the possibility of adaptively sparsifying the model during training without significantly impacting its performance, if we are willing to apply task-specific adaptations to the network weights. Code is available at https://github.com/salomonhotegni/MDMTN.

Thermal and chemical structure of ethanol and 2-ethylhexanoic acid/ethanol SpraySyn flames - Gonchikzhapov, Munko; Kasper, Tina (Applications in Energy and Combustion Science)
Keywords: Nanoparticle synthesis; Flame spray pyrolysis; SpraySyn burner; Flame structure; Species distribution; Temperature distribution

Efficient time stepping for numerical integration using reinforcement learning - Dellnitz, Michael; Hüllermeier, Eyke; Lücke, Marvin; Ober-Blöbaum, Sina; Offen, Christian; Peitz, Sebastian; Pfannschmidt, Karlson (SIAM Journal on Scientific Computing)
Many problems in science and engineering require an efficient numerical approximation of integrals or solutions to differential equations. For systems with rapidly changing dynamics, an equidistant discretization is often inadvisable as it results in prohibitively large errors or computational effort. To this end, adaptive schemes, such as solvers based on Runge–Kutta pairs, have been developed which adapt the step size based on local error estimations at each step. While the classical schemes apply very generally and are highly efficient on regular systems, they can behave suboptimally when an inefficient step rejection mechanism is triggered by structurally complex systems such as chaotic systems. To overcome these issues, we propose a method to tailor numerical schemes to the problem class at hand. This is achieved by combining simple, classical quadrature rules or ODE solvers with data-driven time-stepping controllers. Compared with learning solution operators to ODEs directly, it generalizes better to unseen initial data as our approach employs classical numerical schemes as base methods. At the same time it can make use of identified structures of a problem class and, therefore, outperforms state-of-the-art adaptive schemes. Several examples demonstrate superior efficiency. Source code is available at https://github.com/lueckem/quadrature-ML.

Analysis and Modelling of the Deformation in the Manufacture of Flange-Contours by the Combined Friction-Spinning and Flow-Forming Process - Dahms, Frederik; Homberg, Werner (Lecture Notes in Mechanical Engineering)

Unboxing video effectiveness – Does speech matter? - Garnefeld, I.; Böhm, Eva; Hanf, L.; Helm, S. (2023 AMA Summer Academic Conference, San Francisco, CA)

The dark and bright side of online reviews in manufacturer online shops - Kessing, K.; Garnefeld, I.; Böhm, Eva (EMAC Annual Conference, Odense, Denmark)

Stimulating engagement with unboxing videos – Does speech matter? - Hanf, L.; Garnefeld, I.; Böhm, Eva; Helm, S. (EMAC Annual Conference, Odense, Denmark)

Low Power Streaming of Sensor Data Using Gray Code-Based Approximate Communication - Sadeghi-Kohan, Somayeh; Hellebrand, Sybille; Wunderlich, Hans-Joachim (2023 53rd Annual IEEE/IFIP International Conference on Dependable Systems and Networks Workshops (DSN-W))

Assessing pre-service EFL teachers’ feedback performance in role-play-based simulations - Janzen, Thomas; Wotschel, Philipp; Meier, Jana; Vogelsang, Christoph (EARLI 2023)

Overcoming the Miscibility Gap of GaN/InN in MBE Growth of Cubic InxGa1–xN - Zscherp, Mario Fabian; Jentsch, Silas Aurel; Müller, Marius Johannes; Lider, Vitalii; Becker, Celina; Chen, Limei; Littmann, Mario; Meier, Falco; Beyer, Andreas; Hofmann, Detlev Michael; As, Donat Josef; Klar, Peter Jens; et al. (ACS Applied Materials & Interfaces)
Keywords: General Materials Science

Bring me my Meal on your Wheel - An Empirical Analysis of the Impact of Food Delivery Platforms on Local Restaurant Employment - Müller, Michelle; Neumann, Jürgen (Proceedings of the 55th Hawaii International Conference on System Sciences (HICSS))

Home (Office) is where your Heart is - Marx, Julian; Stieglitz, Stefan; Brünker, Felix; Mirbabaie, Milad (Business & Information Systems Engineering)
Abstract Working conditions of knowledge workers have been subject to rapid change recently. Digital nomadism is no longer a phenomenon that relates only to entrepreneurs, freelancers, and gig workers. Corporate employees, too, have begun to uncouple their work from stationary (home) offices and 9-to-5 schedules. However, pursuing a permanent job in a corporate environment is still subject to fundamentally different values than postulated by the original notion of digital nomadism. Therefore, this paper explores the work identity of what is referred to as ‘corporate nomads’. By drawing on identity theory and the results of semi-structured interviews, the paper proposes a conceptualization of the corporate nomad archetype and presents nine salient identity issues of corporate nomads (e.g., holding multiple contradictory identities, the flexibility paradox, or collaboration constraints). By introducing the ‘corporate nomad’ archetype to the Information Systems literature, this article helps to rethink established conceptions of “home office” and socio-spatial configurations of knowledge work.
Keywords: Information Systems

Aware but not prepared: understanding situational awareness during the century flood in Germany in 2021 - Zander, K.K.; Nguyen, D.; Mirbabaie, Milad; Garnett, S.T. (International Journal of Disaster Risk Reduction)
Keywords: Geology; Safety Research; Geotechnical Engineering and Engineering Geology; Building and Construction

The potential of digital nudging to bridge the gap between environmental attitude and behavior in the usage of smart home applications - Stieglitz, Stefan; Mirbabaie, Milad; Deubel, Annika; Braun, Lea-Marie; Kissmer, Tobias (International Journal of Information Management)
Keywords: Library and Information Sciences; Computer Networks and Communications; Information Systems

Digital Nudge Stacking and Backfiring: Understanding Sustainable E-Commerce Purchase Decisions - Mirbabaie, Milad; Marx, Julian; Erle, Lukas (Pacific Asia Journal of the Association for Information Systems)

Analyse von Alterungsmechanismen im Hinblick auf die Effizienz von Haushaltskältegeräten - Paul, Andreas
Die Energieaufnahme von Haushaltskältegeräten ist seit den 1990er Jahren erheblich gesunken. Dieser Wert wird von den Herstellern im Neuzustand der Geräte unter Normbedingungen bestimmt. Wie jedes technische System unterliegen jedoch auch Haushaltskältegeräte einem Alterungsprozess, der zu einem Anstieg der Energieaufnahme über die Zeit führt. Im Rahmen dieser Dissertation wurde auf der Grundlage von 100 Messungen der Energieaufnahme, die an 32 Geräten über einen Zeitraum von 21 Jahren durchgeführt wurden, ein Alterungsmodell entwickelt. Dieses Modell ist das erste, das mit Hilfe von Daten der Energieaufnahme real gealterter Geräte entwickelt wurde. Es beschreibt einen Anstieg der Energieaufnahme von 27 % über die durchschnittliche Einsatzzeit eines Haushaltskältegeräts von 16 Jahren. Der stärkste Anstieg erfolgt in den ersten fünf Betriebsjahren. Durch Diffusionsvorgänge in dem im Gehäuse verbauten Polyurethan-Schaum wird das im Zellgas vorhandene Kohlenstoffdioxid durch Luft ersetzt. Hierdurch steigt die Wärmeleitfähigkeit des Schaums um ca. 33 % an, wodurch sich die Energieaufnahme der Geräte erhöht. Des Weiteren wurde der Einsatz von Paraffinen als Phasenwechselmaterial in Haushaltskältegeräten untersucht. Durch deren Einsatz konnte die Energieaufnahme gesenkt und die Funktionalität der Geräte gesteigert werden. Hierfür sind detaillierte Kenntnisse der Materialkenndaten der Paraffine notwendig. Die Wärmeleitfähigkeit der verschiedenen Paraffin-Stoffgruppen in der festen Phase ist jedoch bisher nur unzureichend untersucht worden. Daher wurde ein Messaufbau entwickelt, mit dem die Wärmeleitfähigkeit von festem Paraffin bestimmt werden kann, und es wurden entsprechende Messungen durchgeführt.

Second grader´s understanding of doubling and halfing in various representations - Schwerin, Imke; Häsel-Weide, Uta (International Symposium in Elementary Mathematics Teaching. Proceedings: New Directions in Elementary Mathematics Education)

Lehre in Zeiten von Digitalisierung und Inklusion - Beispiele aus drei Fächern - Schmidt, Rebekka; Tenberge, Claudia; Häsel-Weide, Uta (Aktive Teilhabe fördern – ICM und Student Engagement in der Hochschullehre)

How to Speak Silently — Rethinking Materiality, Agency, and Communicative Competence in Virtual Reality - A. Erofeeva, Maria; Klowait, Nils; Zababurin, Denis (Sociology of Power)
Keywords: General Medicine

Investigations on the Influences of the Thermomechanical Manufacturing of Aluminium Auxiliary Joining Elements - Borgert, Thomas; Henke, Maximilian; Homberg, Werner (Journal of Manufacturing and Materials Processing)
The demands on joining technology are constantly increasing due to the consistent lightweight construction and the associated increasing material mix. To meet these requirements, the adaptability of the joining processes must be improved to be able to process different material combinations and to react to challenges caused by deviations in the process chain. One example of a highly adaptable process due to the two-step process sequence is thermomechanical joining with Friction Spun Joint Connectors (FSJCs) that can be individually adapted to the joint. In this paper, the potentials of the adaption in the two-stage joining process with aluminium auxiliary joining elements are investigated. To this end, it is first investigated whether a thermomechanical forming process can be used to achieve a uniform and controlled manufacturing regarding the process variable of the temperature as well as the geometry of the FSJC. Based on the successful proof of the high and good repeatability in the FSJC manufacturing, possibilities, and potentials for the targeted influencing of the process and FSJC geometry are shown, based on an extensive variation of the process input variables (delivery condition and thus mechanical properties of the raw parts as well as the process parameters of rotational speed and feed rate). Here it can be shown that above all, the feed rate of the final forming process has the strongest influence on the process and thus also offers the strongest possibilities for influencing it.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Friction-Induced Recycled Aluminium Semi-finished Products in Thermo-mechanical Joining Technology - Borgert, Thomas; Homberg, Werner (Lecture Notes in Mechanical Engineering)
Due to current global challenges regarding energy security as well as climate change the importance of preserving the nature and all available resources is steadily increasing. In order to achieve the energy-saving and climate targets, it is not only necessary to develop new processes and processing possibilities, but also to optimise known process chains with regard to energy and resource efficiency in the area of production technology. Here, the recycling of supposed production waste represents an opportunity to save energy. In addition to the conventional and smelting metallurgical recycling process, extensive research activities have therefore been carried out for alternative solid-state recycling processes. One example is the friction-induced recycling process, which has been used in past studies to demonstrate the energy- and resource-efficient production of semi-finished products from aluminium scrap such as chips. In addition, properties like chemical composition and strength can be adjusted locally and in terms of processing time. This can be used to improve the versatility of further processing steps.

Mit dem Leben Schritt halten - Eine Analyse des Wearable-Dispositivs - Schloots, Franziska Margarete
„Lerne deinen Körper besser kennen“, „Das Beste für deine Gesundheit“ und „Ihre Transformation beginnt jetzt“ - mit Versprechen wie diesen vermitteln die Produkttexte von Wearables wie Fitnesstracker und Smartwatches ein ganz bestimmtes Bild ihrer vorgesehenen Nutzer*innen und deren Nutzung. Verbunden mit den kleinen, am Handgelenk getragenen Geräten sind Fragen nach Erkenntnisgewinn und Kontrollverlust, Selbstoptimierung und Quantifizierungslogiken, Eigenverantwortung und Fremdsteuerung. Die vorliegende Arbeit widmet sich diesem komplexen Spannungsfeld und verfolgt dabei einen multiperspektivischen Ansatz: im Rahmen einer Dispositivanalyse werden die einzelnen Elemente des Wearable-Dispositivs als eigenständige, empirisch zu untersuchende Analysegegenstände betrachtet, um so das Zusammenwirken und die komplexe Beziehung von Diskursen, Gegenständen, Nutzung, Subjekten und Gesellschaft zu erforschen. Ein besonderes Erkenntnisinteresse liegt dabei auf dem Wissen, was sich über Wearables etabliert hat und sich in den Alltagspraktiken der Nutzer*innen widerspiegelt sowie bei der Frage nach den möglichen Funktionen und Auswirkungen des Wearable-Dispositivs.
Keywords: Selbstvermessung; Dispositivanalyse; Gesundheitsdiskurs; Quantifizierungsgesellschaft; Wearables; Selbstoptimierung

Mesh- and model adaptivity for elasto-plastic mean-field and full-field homogenization based on downwind and upwind approximations - Tchomgue Simeu, Arnold; Mahnken, Rolf (XI International Conference on Adaptive Modeling and Simulation)

Digital technology usage as a driver of servitization paths in manufacturing industries - Harrmann, Lisa Katharina; Eggert, Andreas; Böhm, Eva (European Journal of Marketing)
Purpose This study aims to conceptually propose and empirically validate a path perspective on the servitization process of manufacturing firms. It identifies a customer and an outcome path to servitization, sheds light on the pivotal role of digital technology usage for both value-creating paths and explores their financial and relational performance outcomes. Design/methodology/approach The authors use a mixed-method approach, combining a qualitative study with a cross-sectional survey in the USA, the UK and Germany. Findings Manufacturing firms choose between two generic paths to servitization, a customer and an outcome path. Digital technology usage is equally important for both value-creating paths. Progress on the outcome path has a positive effect on firms’ financial performance, whereas the customer path has an indirect effect only, fully mediated by firms’ relational performance. Customer tenure and customer’s open-mindedness are contingency variables in the digital technology usage – servitization path – firm performance framework. Research limitations/implications A path perspective is useful to conceptualize the servitization processes in manufacturing industries. Future research should investigate the sequential choice of servitization paths and explore its drivers and performance outcomes. Practical implications To create and claim superior value for their customers, managers can choose between two servitization paths, leading to differential performance outcomes. While digital technology usage is key to progress on both paths, it is particularly effective for newly acquired customers on the customer path. Suppliers should target their value-creating service offerings at open-minded customer firms to reap their full performance potential. Originality/value Propose and empirically validate a path-perspective on servitization. Understand the pivotal importance of digital technology usage for both servitization paths.
Keywords: Marketing

Der Hauptschulabschluss als sozial selektiver Hauptzulieferer des Übergangssystems - Sommer, Christian (Berufsbildung. Zeitschrift für Theorie-Praxis-Dialog)
Über zwei Drittel der Anfänger*innen im Übergangssystem verfügen maximal über einen Hauptschul-/Mittelschulabschluss. Sie sind damit überrepräsentiert, was sich weniger durch ihre Kompetenzen als mit ihrem sozioökonomischen Status und klassenspezifischen Nachqualifizierungsverhalten erklären lässt.
Keywords: Social inequality; Transition system

»In der Art von Inschriften«. Emblematische Inschriftendichtung als Darstellungsprinzip von Ferdinand von Fürstenbergs Monumenta Paderbornensia (1669 und 1672) - Süßmann, Johannes (Monumenta. Erinnerungsorte zwischen Weser und Lippe. Die Monumenta Paderbornensia des Ferdinand von Fürstenberg)

Perceptions of inclusion in students with diagnosed behavioural, emotional and social difficulties (BESD) displaying internalising and externalising behaviour in inclusive and special education - Zdoupas, Philippos; Laubenstein, Désirée (European Journal of Special Needs Education (Latest Articles))

Entwicklungszielgespräche in der Sekundarstufe I - Systemisches Coaching mit Schüler:innen nach dem GROW-Modell - Zdoupas, Philippos; Lara, Kuhlhoff; Martin, Grust; Jaekel, Anne-Marie; Jan, Ehlert

Predicting the development of digital media PCK/TPACK: The role of PCK, motivation to use digital media, interest in and previous experience with digital media - Schubatzky, Thomas; Burde, Jan-Philipp; Große-Heilmann, Rike; Haagen-Schützenhöfer, Claudia; Riese, Josef; Weiler, David (Computers & Education)
Keywords: Education; General Computer Science